Effects of Dissolved Organic Matter on Sorption of Oxytetracycline to Sediments - Zongzhou Wang; Qianli Jiang; Runze Wang; Xiaoyu Yuan; Shengke Yang; Wenke Wang; Yaqian Zhao (Geofluids)
The effects of two representative dissolved organic matters (DOMs) (derived from corrupt plants (PDOM) and chicken manure (MDOM)) on sorption characteristic of oxytetracycline to three typical sediments (first terrace (FT), river floodplain (RF), and riverbed (RB) sediments collected from the Weihe River) were investigated. Results showed that both DOMs can make the adsorption equilibrium time advance about 6 hours. The presence of DOMs changed the sorption kinetics model and the spontaneous degree of the reaction but did not change the sorption isotherm models. The adsorption of oxytetracycline (OTC) could be promoted by adding PDOM, and its maximum adsorption amount increased by 23.8% for FT, 38.0% for RB, and 28.3% for RF, respectively, whereas MDOM could inhibit the adsorption and maximum adsorption amount decreased by 23.3% for FT, 11.6% for RB, and 16.1% for RF, respectively. In addition, the DOM concentration also affected the adsorption. Overall, this study suggests that the humus-like DOM can promote the adsorption of OTC while the protein-like DOM can inhibit the adsorption of OTC to sediments, which is determined by the aromaticity, hydrophilicity, and polarity of the DOMs.